Marlowe, Shakespeare, and the economy of theatrical experience - Cartelli, Thomas (University of Pennsylvania Press, 1991)
This study explores the structure of psychological, social and political exchanges that were negotiated between audiences and plays in Elizabethan public theatres in a period ostensibly dominated by Shakespeare, but strongly rooted in Marlowe.